Association of ANA and SSA autoantibodies with progression-free survival in multiple myeloma: a retrospective cohort study - Zhang, Jiafeng; Ren, Hefei; Chen, Lei; Wang, Xin; Wang, Huiquan; Wu, Hongkun; Zhou, Lin (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to investigate the relationship between autoantibodies, specifically Antinuclear Antibody (ANA) and anti-Sjögren’s-syndrome-related antigen A (SSA), and progression-free survival (PFS) in multiple myeloma (MM) patients.MethodsA retrospective cohort study was conducted on 304 MM patients diagnosed between 2010 and 2020 at Shanghai Changzheng Hospital, with follow-up until October 2023. Patients were stratified based on ANA and SSA positivity. Clinical data were analyzed using Kaplan-Meier survival curves and Cox regression models, adjusting for key prognostic factors. Sensitivity analyses were performed using propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) to evaluate the robustness of the results.ResultsSSA-positive patients exhibited significantly shorter PFS compared to SSA-negative patients (17 vs. 44 months, HR = 2.93, 95% CI 1.53-5.64, p = 0.001), while ANA positivity was associated with a smaller increase in risk (HR = 1.57, 95% CI 1.04-2.4, p = 0.034). The impact of SSA remained significant after adjusting for various covariates in the Cox regression model and sensitivity analyses. Subgroup analyses revealed consistent effects of SSA positivity across different demographic and clinical factors.ConclusionSSA positivity is associated with a higher risk of disease progression in MM patients, suggesting it may serve as a valuable prognostic marker. The relationship between autoantibodies and MM prognosis warrants further investigation in larger, multicenter studies to elucidate the underlying mechanisms and inform clinical management.